Uncertainty Avoiding Cultural Distance and Foreign Direct Investment Entry Pattern (Journal of Global Humanities and Social Sciences, 2024)
With the gradual development of economic globalization and the continuous call of China's "Belt and Road Initiative" initiative, the scale of Chinese enterprises' foreign direct investment will further expand, and enterprises face various cultural nuances when conducting foreign direct investment. Among them, the impact of uncertainty avoiding cultural distance on the choice of investment entry mode is particularly significant. In the process of foreign direct investment, enterprises will inevitably face cultural exchanges and collisions between different regions and countries, and differences in languages, cultures, religious beliefs, and values among regions will constitute important factors affecting Chinese enterprises' foreign direct investment. In addition, there are many factors that affect enterprises' OFDI. This paper will sort out the relevant literature on the relationship between cultural distance, host country factors, parent company factors and OFDI entry mode, and briefly expound and explain the role and theory of these influencing factors.